2022
DOI: 10.3389/fimmu.2022.1049936
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis increases obesity: Crosstalk between adipocytes and the neuroimmune system

Abstract: Ferroptosis requires not only the accumulation of iron ions, but also changes in many ferroptosis-related regulators, including a decrease in GPX4 and inhibition of SLC7A11 for classical ferroptosis, a deletion of FSP1 or GCH1. Surprisingly, adipose tissue (AT) in the obesity conditions is also accompanied by iron buildup, decreased GSH, and increased ROS. On the neurological side, the pro-inflammatory factor released by AT may have first caused ferroptosis in the vagus nerve by inhibiting of the NRF2-GPX4 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 175 publications
0
13
0
Order By: Relevance
“…It has been found that obesity is closely related to the disturbance of iron metabolism, mainly characterized by high ferritin levels ( 78 ). Ferroptosis caused by iron accumulation is accompanied by elevated ROS, decreased GSH and inflammatory reactions, insulin resistance and mitochondrial dysfunction, leading to metabolic disorders and the development of obesity ( 79 81 ). In terms of immunity, obesity may lead to ferroptosis in Tregs and B1 cells by reducing the levels of NRF2, GPX4 and GCH1 ( 80 , 82 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that obesity is closely related to the disturbance of iron metabolism, mainly characterized by high ferritin levels ( 78 ). Ferroptosis caused by iron accumulation is accompanied by elevated ROS, decreased GSH and inflammatory reactions, insulin resistance and mitochondrial dysfunction, leading to metabolic disorders and the development of obesity ( 79 81 ). In terms of immunity, obesity may lead to ferroptosis in Tregs and B1 cells by reducing the levels of NRF2, GPX4 and GCH1 ( 80 , 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis caused by iron accumulation is accompanied by elevated ROS, decreased GSH and inflammatory reactions, insulin resistance and mitochondrial dysfunction, leading to metabolic disorders and the development of obesity ( 79 81 ). In terms of immunity, obesity may lead to ferroptosis in Tregs and B1 cells by reducing the levels of NRF2, GPX4 and GCH1 ( 80 , 82 ). In our previous study, biological processes such as fatty acid and glucose metabolism were also enriched in ferroptosis cluster A.…”
Section: Discussionmentioning
confidence: 99%
“…The enzymatic process involved in the reaction is mainly lipoxygenase but also requires the participation of acetyl coenzyme A synthase long-chain family 4 (ACSL4) and lysophosphatidyl choline acyltransferase 3 (LPCAT3), which is associated with lipid remodelling (42). The reaction uses free PUFAs arachidonic acid as the primary phospholipid substrate, which is finally oxidized by lipoxygenase to form lipid peroxides after two-step esterification by ACSL4 and LPCAT3 (43).…”
Section: Lipid Peroxide Aggregationmentioning
confidence: 99%
“…Furthermore, ferroptosis is closely related to many disease processes, such as oxidative stress, 32 inflammatory response 33 and autophagy 34 . In particular, ferroptosis is involved in the pathological process of obesity 35 . Excessive nutrient intake and fat storage in white adipose tissue (WAT) ultimately leads to obesity.…”
Section: Introductionmentioning
confidence: 99%
“…34 In particular, ferroptosis is involved in the pathological process of obesity. 35 Excessive nutrient intake and fat storage in white adipose tissue (WAT) ultimately leads to obesity. Insufficient iron intake is also linked to overweight or obesity in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%